Photoexcitation effects in YBa2Cu3Ox - Osquiguil, E.; Maenhoudt, M.; Wuyts, B.; Bruynseraede, Y.; Lederman, D.; Nieva, G.; Guimpel, J.; Schuller, I.K.; Guimpel, Julio; Nieva, Gladys (Elsevier, 1993)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Katholieke Univetsiteit Leuve; Bélgica